Quay crane scheduling in container terminals - Chan, Samson Yan Liang (2017)
In this report, a heuristic quay crane scheduling algorithm is designed to tackle the problem of determining the best allocation of quay cranes to bays of a particular container ship. Each bay consists of a number of jobs based on the number of containers that are to be loaded or unloaded from that particular bay. The quay cranes will be allocated to more or less work relative to its adjacent cranes. This is dependent on the workload of the quay cranes in proximity to it. Also, the jobs in a bay may be split in 2 parts, where it will be handled by 2 cranes, should this prove to be more efficient. The objective is to balance the workloads among quay cranes and to reduce the turnaround time for the whole ship. In this report, the algorithm will repeatedly search for a better solution until a reasonable one is found, or stop when a better solution has not been found after a set number of times.